Climate change and liver disease: a mini review - Ribeiro, Tiago; Macedo, Guilherme (Frontiers in Gastroenterology, 2024)
Climate change poses a growing threat to human health and well-being, with emerging evidence pointing to its intricate relationship with liver diseases. Indeed, climate change influences liver diseases through various direct and indirect mechanisms. Alcohol-related liver disease, Metabolic dysfunction-associated liver disease (MASLD), and viral hepatitis are the three most common causes of liver disease, and all are susceptible to the effects of climate change. Shifts in dietary habits driven by altered food availability, substance abuse exacerbated by social instability, extreme weather events affecting healthcare access, and the emergence of waterborne infections are among the factors exacerbating liver disease incidence and severity. On the flip side, healthcare systems, including liver units, significantly contribute to climate change through energy consumption, medical waste, and transportation emissions. The need for sustainable healthcare practices, telemedicine, and waste reduction strategies is becoming increasingly evident. Recognizing this intricate interplay and addressing the dual interaction between climate change and liver disease is imperative for safeguarding human health and reducing the environmental footprint of healthcare facilities. As climate change continues to unfold, understanding its implications for liver disease is critical for public health and environmental sustainability.